Quantification of the distortion present in the postero-anterior cephalogram - Janneth Rocio Zúñiga Prado; Elizabeth Peña Tobar; Gloria Patricia Baena-Caldas (Editorial Ciencias Médicas, 2019)
Introduction: Universally, it has been accepted that the postero-anterior cephalogram presents less distortion than any other x-ray radiograph; for this reason, the measurements taken on it are considered reliable. Objective: To determine for a postero-anterior cephalogram, what percentage of distortion is present in different regions of the skull and mandible. Methods: Thirty human skulls with their mandibles were divided by three horizontal and four vertical planes in fifteen quadrants, resulting ten in the skull and five in the mandible. In each quadrant, one vertical and one horizontal steel wire were fixed and their lengths were measured (real value). To each set, a postero-anterior cephalogram was taken and the wire images were measured (radiograph value). Results: No measurement could be taken in the lateral quadrants of the skull. The horizontal measurement in the right and left intermediate inferior quadrants of the skull and in the right and left intermediate and lateral quadrants of the mandible is not reliable; in the median quadrant of the mandible it is minimized; in the median and intermediate superior right and left quadrants of the skull and median quadrant of the mandible it is magnified. The vertical measurement in all the quadrants is reliable; in the right and left intermediate superior quadrants of the skull and right and left intermediate and lateral quadrants of the mandible it is magnified; in the right and left intermediate inferior and median superior and inferior quadrants of the skull and median quadrant of the mandible it is minimized. The minimum distortion for both measurements is present in the median superior quadrant of the skull. The percentage of distortion in each quadrant for both measurements is reported. Conclusions: Distortion is present in the postero-anterior cephalogram and it varies from one region to another of the face.